2021
DOI: 10.18332/tid/133054
|View full text |Cite
|
Sign up to set email alerts
|

Measuring fidelity to delivery of a new smoking cessation intervention integrated into routine tuberculosis care in Pakistan and Bangladesh: Contextual differences and opportunities

Abstract: INTRODUCTION Tobacco smoking among tuberculosis (TB) patients leads to poorer treatment outcomes. Smoking cessation support should be integrated into routine TB care. We measured healthcare providers’ fidelity to a smoking cessation intervention integrated into routine TB care, in Bangladesh and Pakistan. We aimed to understand the role of providers and settings in the implementation of behavior support (BS) messages for TB and smoking cessation. METHODS The integrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
2
1
Order By: Relevance
“…It was unclear, however, why participants in the cytisine arm reported more and longer hospital stays than the placebo arm in Pakistan. Our process evaluation study found some difference in intervention delivery between countries,36 37 but we did not find evidence of differential TB treatment outcomes between trial arms in Pakistan,10 and the same situation was not observed in Bangladesh. This might indicate a potential country-related contextual reason rather than the effect of the intervention or occurrence by chance.…”
Section: Discussioncontrasting
confidence: 80%
“…It was unclear, however, why participants in the cytisine arm reported more and longer hospital stays than the placebo arm in Pakistan. Our process evaluation study found some difference in intervention delivery between countries,36 37 but we did not find evidence of differential TB treatment outcomes between trial arms in Pakistan,10 and the same situation was not observed in Bangladesh. This might indicate a potential country-related contextual reason rather than the effect of the intervention or occurrence by chance.…”
Section: Discussioncontrasting
confidence: 80%
“…This will involve quantifying each ‘critical decision-making point’ (for example, whether antibiotic review was conducted within 48–72 h of initial prescription) into a 3-point rating scale that reliably discriminates between ‘fully’, ‘partially’ and ‘not implemented’. Although successfully used previously [ 22 24 ] these categories might not apply to ePAMS+. The feasibility work will help confirm these categories or explore alternatives such as codifying into ‘present’, ‘absent but should be present’ and ‘not applicable’ [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…This will involve quantifying each 'critical decision-making point' (for example, whether antibiotic review was conducted within 48-72 hours of initial prescription) into a 3point rating scale that reliably discriminates between 'fully', 'partially' and 'not implemented'. Although successfully used previously, [19][20][21] these categories might not apply to ePAMS+. The feasibility work will help confirm these categories or explore alternatives such as codifying into 'present', 'absent but should be present' and 'not applicable'.…”
Section: Develop Individual and Composite Scales For Capturing Practicementioning
confidence: 99%